Does muscle mass affect running performance in male long-distance master runners? - Knechtle, B.; Rüst, C. A.; Knechtle, P.; Rosemann, T. (Asian Journal of Sports Medicine, 2012)
Purpose: The aim of the present study was to investigate associations between skeletal muscle mass, body fat and training characteristics with running times in master athletes (age > 35 years) in half-marathon, marathon and ultra-marathon.